A population-based study of social demographic factors, associated diseases, and herpes zoster ophthalmicus in Taiwan - Lee, Chia-Yi; Chang, Yuh-Shin; Ho, Chung-Han; Wang, Jhi-Joung; Jan, Han-Yi; Lee, Po-Han; Jan, Ren-Long (Frontiers in Medicine, 2025)
IntroductionHerpes zoster ophthalmicus (HZO) occurs due to the reactivation of latent varicella-zoster virus (VZV) and is characterized by the involvement of the ophthalmic branch of the trigeminal nerve. While this pathophysiology is well-established, the precise mechanisms driving VZV reactivation remain incompletely understood. Furthermore, it is unclear whether individuals with common comorbidities that compromise immune function face an elevated risk of developing HZO. Investigating potential links between HZO and chronic systemic conditions holds significant importance from public health, medical, and scientific perspectives. To address these gaps, we conducted a study to examine the association between HZO development, sociodemographic factors, and systemic comorbidities.Materials and methodsThis nationwide, population-based, retrospective, matched case-controlled study included 52,112 patients with HZO (identified by the International Classification of Diseases, Ninth Revision, Clinical Modification code 053.2 for herpes zoster with ophthalmic complications) from the Taiwan National Health Insurance Research Database. The age-, sex-, and index date-matched control group included 52,112 non-HZO individuals from the Taiwan Longitudinal Health Insurance Database 2000. Sociodemographic factors and associated systemic diseases were examined using univariate logistic regression analyses, and continuous variables were analysed using paired t-tests. The odds ratios (ORs) for developing HZO were compared using adjusted logistic regression analysis.ResultsPatients with systemic diseases (hypertension, diabetes, hyperlipidaemia, etc.) had significantly higher ORs for HZO development. Patients whose monthly income was >NT 30,000 and patients residing in southern Taiwan had increased odds of developing HZO; however, patients residing in northern Taiwan, metropolitans, or satellite cities, and being public servants (military, civil, teaching staff, etc.) had decreased odds of developing HZO.DiscussionHZO is strongly associated with hypertension, diabetes mellitus, hyperlipidaemia, coronary artery disease, chronic renal disease, and human immunodeficiency virus infection. These findings emphasise the role of systemic health in HZO risk.